2008
DOI: 10.1038/ijo.2008.211
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain by reduced brain melanocortin activity affects offspring energy balance in rats

Abstract: Introduction: Excessive gestational body weight gain of mothers may predispose offspring towards obesity and metabolic derangements. It is difficult to discern the effects of maternal obesogenic factorsFsuch as diet and/or thrifty genetic predispositionFfrom gestational weight gain per se. Methods: For this reason, genetically normal Wistar rats that were fed regular chow were rendered hypothalamically obese by chronic third-cerebral ventricular (i3vt) infusion during pregnancy and lactation with the melanocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…While our observation of a loss of response to α‐MSH during pregnancy seems quite clear, these data are not supported by a previous study using chronic third‐cerebral ventricular infusion of SHU9119, a melanocortin‐3,4 receptor blocker. That study found that SHU9119 administered from day 4 of pregnancy significantly increased food intake and weight gain during pregnancy, suggesting that there is ongoing melanocortin tone (Heinsbroek & van Dijk, ). It seems likely that this apparent contradiction is explained by the different timing in the two experiments.…”
Section: Discussionmentioning
confidence: 99%
“…While our observation of a loss of response to α‐MSH during pregnancy seems quite clear, these data are not supported by a previous study using chronic third‐cerebral ventricular infusion of SHU9119, a melanocortin‐3,4 receptor blocker. That study found that SHU9119 administered from day 4 of pregnancy significantly increased food intake and weight gain during pregnancy, suggesting that there is ongoing melanocortin tone (Heinsbroek & van Dijk, ). It seems likely that this apparent contradiction is explained by the different timing in the two experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is an anorexigenic hormone secreted by adipose tissue and the placenta, but its main function is in the hypothalamus, decreasing appetite and food intake (42). Heinsbroek and van Dijk (43) showed in rats that brain melanocortin receptor blockade during pregnancy induced GWG and increased the body weight of offspring postnatally; the melanocortin receptor blockade can alter leptin and anorexigenic effects in rats, leading to postnatal obesity (44). In addition to rat models, a mouse model has supported the hypothesis that a high-fat diet in obese female mice can alter both adiposity and DNA hypomethylation of inflammation-associated genes in offspring (45).…”
Section: Discussionmentioning
confidence: 99%
“…A simple increases in body weight gain during pregnancy and lactation due to hyperphagia induced by pharmacological inhibition of melanocortin 3/4 receptor leads to the development of obesity in offspring over time (Heinsbroek et al, 2009). Animal study suggests that overnutrition either starting prior to gestation or from gestation and lactation exert similar effect on the development of obesity and hyperinsulinemia in offspring (Howie et al, 2008), suggesting the critical windows of fetal development that determines the phenotype.…”
mentioning
confidence: 99%